IDNLearn.com is designed to help you find reliable answers quickly and easily. Our experts provide timely and precise responses to help you understand and solve any issue you face.
Sagot :
Let's solve the system of equations step-by-step using the substitution method.
The given system of equations is:
[tex]\[ \begin{array}{l} 6x - y = 1 \quad \text{(1)} \\ 4x - 3y = -11 \quad \text{(2)} \end{array} \][/tex]
1. Solve the first equation for [tex]\(y\)[/tex]:
[tex]\[ 6x - y = 1 \][/tex]
[tex]\[ -y = 1 - 6x \][/tex]
[tex]\[ y = 6x - 1 \][/tex]
2. Substitute [tex]\(y = 6x - 1\)[/tex] into the second equation (Equation 2):
[tex]\[ 4x - 3(6x - 1) = -11 \][/tex]
Now let's verify which of the given choices corresponds to this substitution. Simplify the above equation step by step:
[tex]\[ 4x - 3(6x - 1) = -11 \][/tex]
[tex]\[ 4x - 18x + 3 = -11 \][/tex]
Simplify further if necessary, but at this step, the new equation after substituting [tex]\(y\)[/tex] from the first equation into the second equation clearly matches:
[tex]\[ 4x - 3(6x - 1) = -11 \][/tex]
So, the correct choice is:
[tex]\[ 4x - 3(6x - 1) = -11 \][/tex]
Therefore, the answer is indeed [tex]\(\boxed{4 x-3(6 x-1)=-11}\)[/tex].
The given system of equations is:
[tex]\[ \begin{array}{l} 6x - y = 1 \quad \text{(1)} \\ 4x - 3y = -11 \quad \text{(2)} \end{array} \][/tex]
1. Solve the first equation for [tex]\(y\)[/tex]:
[tex]\[ 6x - y = 1 \][/tex]
[tex]\[ -y = 1 - 6x \][/tex]
[tex]\[ y = 6x - 1 \][/tex]
2. Substitute [tex]\(y = 6x - 1\)[/tex] into the second equation (Equation 2):
[tex]\[ 4x - 3(6x - 1) = -11 \][/tex]
Now let's verify which of the given choices corresponds to this substitution. Simplify the above equation step by step:
[tex]\[ 4x - 3(6x - 1) = -11 \][/tex]
[tex]\[ 4x - 18x + 3 = -11 \][/tex]
Simplify further if necessary, but at this step, the new equation after substituting [tex]\(y\)[/tex] from the first equation into the second equation clearly matches:
[tex]\[ 4x - 3(6x - 1) = -11 \][/tex]
So, the correct choice is:
[tex]\[ 4x - 3(6x - 1) = -11 \][/tex]
Therefore, the answer is indeed [tex]\(\boxed{4 x-3(6 x-1)=-11}\)[/tex].
Thank you for using this platform to share and learn. Keep asking and answering. We appreciate every contribution you make. Find the answers you need at IDNLearn.com. Thanks for stopping by, and come back soon for more valuable insights.